UNELE ASPECTE ALE SISTEMULUI SANGVIN LA INFLUENŢA STRESULUI - Melnic, Boris; Paladi, Ecaterina; Budeanu, Liuba (CEP USM, 2008)
This paper deals with the action of the combined stress (hypokinezia and hypotermia (20 -50 C) upon some indexes ofhaematology. The results of the experiments showed an increase of the quantity of the haemoglobin and a decrease ofthe number of red cells and leucocytes.
Keywords: indici hematologici; hipokinezie; hipotermie